Analysis of Incoming Switchgear 3 KV 23-PSW-01B In Substation 23 at PT Kilang Pertamina Refinery Unit VI Balongan - Susatyo Handoko; Abdul Syakur (Institute of Educational, Research, and Community Service)
Switchgear is a set of distribution panel systems that enable the process of switching or disconnecting and connecting loads, both individual and group loads. At PT Kilang Pertamina International Refinery Unit VI Balongan in Substation 23, the operational mechanism of the 3 kV Incoming Switchgear 23-PSW-01B breaker is equipped with a tripping coil to open the circuit during a fault and a closing coil to reconnect the power flow when conditions are safe. The tripping coil mechanism is activated by a lockout relay (F6) that receives signals from the protection relay during a fault, cutting off the power flow to protect the equipment. Conversely, the closing coil reconnects the power flow when all normal conditions are met. This switchgear is equipped with various types of Current Transformers (CT) for current measurement and protection relays such as Over Current Relay (OCR), Neutral Over Current Relay, Ground Over Current Relay, and Under Voltage Relay. The entire system is designed to maintain the reliability of power distribution and protect industrial equipment at the refinery.